Gait kinematics at trot before and after repeated ridden exercise tests in young Friesian stallions during a fatiguing 10-week training program - Siegers, Esther W.; Parmentier, Jeanne I. M.; Sloet van Oldruitenborgh-Oosterbaan, Marianne M.; Munsters, Carolien C. B. M.; Serra Bragança, Filipe M. (Frontiers in Veterinary Science, 2025)
BackgroundAppropriate training is essential for equine athletes to improve fitness and ensure welfare. Young Friesian stallions must complete a 10-week training program for acceptance as breeding stallions. Earlier, this training program was demonstrated to induce overtraining.ObjectivesTo evaluate how this training program affects stallions’ trot locomotion variables in relation to fatigue.Study designProspective analytical study.Methods3 or 4 years-old (n = 16) Friesian stallions performed three ridden indoor standardized exercise tests (SETs) in week-1 (SET-I; n = 15), week-6 (SET-II; n = 11) and week-10 (SET-III; n = 4), measuring heart rate (bpm) and lactate concentration (LA, mmol/L). Before and after each SET, stallions’ locomotion was measured with seven inertial sensors (EquiMoves, 200 Hz) during in-hand trot on a straight line. Stride characteristics, limb angular changes, and upper body kinematics were calculated. The within-measurement coefficient of variation (CV) was calculated for all parameters. Linear mixed models were used to analyze gait variables related to SET, pre-or post-SET and a peak LA ≥4 mmol/L during SETs.ResultsHorses showed individual responses in gait kinematics to moderate fatigue. The range of motion of the withers (ROMwithers) increased post SET-II and SET-III compared to post SET-I. In horses reaching LA ≥ 4 mmol/L, CV increased post SETs for several stride characteristics and upper body asymmetry. Upper body vertical movement asymmetry was above the described reference ranges in 69% of the horses.Main limitationsNumber of horses used and only four horses managed to complete the 10-week training program as breeding stallions.ConclusionThe young Friesian stallions showed individually different responses in absolute gait kinematics after exercise and during an intense training program. The increased ROMwithers and CV of stride characteristics after SETs suggest an acute effect of fatigue on the locomotion pattern. Further investigation is warranted for the pronounced upper body movement asymmetry related to published asymmetry reference values.